Medical entities: Financing types and sources in light of the act on medical activity - Małgorzata Paszkowska (e-Finanse: Financial Internet Quarterly, 2013)
Defining legally permitted financing sources is fundamental for each medical entity. The act on medical activity of 15th April 2011introduced many changes for medical service suppliers also as concerns the permitted financing sources. This paper aims to present the types of medical entities and their financing sources in the light of the new regulations, i.e. the act on medical activity.
Keywords: I11; I15; I18; 330; Poland; health care; financing system